2017
DOI: 10.1364/ol.42.005286
|View full text |Cite
|
Sign up to set email alerts
|

Tens of hertz narrow-linewidth laser based on stimulated Brillouin and Rayleigh scattering

Abstract: We proposed and demonstrated a linewidth compression method of a laser based on stimulated Brillouin scattering (SBS) and a Rayleigh backscattering structure (RBS). The relationship between the output SBS laser linewidth and the input pump linewidth was studied theoretically and experimentally. It is shown that the narrower linewidth of the pump laser leads to the narrower bandwidth of the SBS gain and, finally, the bandwidth of the SBS will tend to its intrinsic value as the linewidth of a pump laser narrower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Taking into account the intrinsic Stokes laser linewidth, the Stokes laser linewidth would never go narrower beyond the quantum noise limit even if the pump laser with the linewidth tending to 0. To address this issue, a correction factor αΔv ef f B related to the effective Brillouin gain spectrum can be introduced for the derivation of the Stokes laser linewidth [28],…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the intrinsic Stokes laser linewidth, the Stokes laser linewidth would never go narrower beyond the quantum noise limit even if the pump laser with the linewidth tending to 0. To address this issue, a correction factor αΔv ef f B related to the effective Brillouin gain spectrum can be introduced for the derivation of the Stokes laser linewidth [28],…”
Section: Theorymentioning
confidence: 99%
“…Alternatively, distributed random feedback from fiber-optic structures with artificially introduced disorder, e.g., random fiber gratings [26], [27] were also used to overwhelm the traditional weak Rayleigh backscattering, yielding the coherent time extension of the generated laser photons with ultra-narrow linewidth. It has been demonstrated that the BRFL eventually allows a lowcost linewidth compressor with respect to a cavity-based pump laser of kHz linewidth, allowing ∼75 Hz ultra-narrow linewidth random lasing radiation with a high side-mode suppression ratio [28]. Up to now, all previous BRFLs were investigated based on a classical cavity-based pump laser, meanwhile, the impact of the pump on the linewidth compression in cascading BRFLs remains ambiguous.…”
mentioning
confidence: 99%
“…Therefore, the laser linewidth can be adjusted by the injection power [ 13 ]. The SBS effect can realize the SLM operation due to the ultra-narrow gain range and generate an ultra-narrow laser linewidth because of the high Q value [ 14 ]. Normally, a long single-mode fiber (hundreds of meters) is necessary for exciting SBS because of the small Brillouin gain coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we investigated Rayleigh backscattering (RBS) in different types of optical fibers and some applications of Rayleigh scattering such as narrower filter, have be attained 10,11 . Moreover, we applied the characteristic of the RBS to the field of narrow linewidth lasers, precisely for attaining deep compression of the laser linewidth 12 . In this process, the spectrum evolution (SpE) characteristics of the RBS are the fundamental approach employed to realize a compressed laser linewidth.…”
Section: Introductionmentioning
confidence: 99%